HER2/neu status detection in breast carcinoma: Is FISH the preferred approach over IHC - Attiya P. Harit; Chethana Babu K; Karthik S. Udupa; Jackson Randolph; Gopika; Andrew Galligan (Tropical Journal of Pathology and Microbiology, 2019)
Background: HER2/neu amplification is found in 15-30% of all breast cancer patients, which can be detected by either immunohistochemistry (IHC) or fluorescence in situ hybridization (FISH). The concordance of FISHand IHC analysis for HER2/neu amplification remains limited, especially with studies in the Indian population. There is a need to further classify this information as HER2/neu positive patients often have a worse disease prognosis and require anti-HER2/neu therapy.Methods: In aretrospective study 149 patients with invasive ductal carcinoma (IDC) and invasive lobular carcinoma (ILC), who underwent bothIHC and FISH testing for HER2/neu amplification were analysed to determine the concordance between the two tests in this population.Results: Out of 149 patients reviewed, 58 had equivocal results on IHC, 52 patients had negative results and 39 patients had positive results on IHC. Analysis of the 91 non-equivocal IHC cases and their FISH results demonstrated an inter-rater reliability of Kappa= 0.606 (p <0.0005) 95% CI (0.445, 0.767). Of the 52 patients with negative IHC scores, 13 (25%) were found to be positive on FISH testing for HER/neu amplification. This represents a substantial number of patients who otherwise would not have received anti-HER2/neu therapy.Conclusions: The present results indicate that FISH testing for HER2/neu status should be done on all breast cancer patients whenever possible, irrespective of IHC score status so that appropriate treatment decisions can be made. The higher sensitivity and specificity ofFISH testing can reduce the number of both false positive and false negatives seen with immunohistochemistry testing in the present study.